2014
DOI: 10.1021/jf503754q
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Astaxanthin on Free Radical Scavenging Capacity and Nitrite Stress Tolerance of Postlarvae Shrimp, Pleoticus muelleri

Abstract: The aim of this study was to investigate the effect of astaxanthin feed supplementation and environmental nitrite stress in postlarvae of Pleoticus muelleri (15 ± 0.004 mg initial weight) under culture conditions. Diets containing three levels of astaxanthin, 0 mg kg(-1) of diet (C0), 100 mg kg(-1) of diet (C(100)), and 300 mg kg(-1) of diet (C(300)), were used. Postlarvae fed with each diet were exposed to different concentrations of nitrite (NO(2)Na) (0-200 mg L(-1)). The 96 h median lethal concentration (LC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…The potential antioxidant activity of postlarval extracts was determined on the basis of the scavenging activity of the stable 1,1‐diphenyl‐2‐picryhydrazyl (DPPH) free radical, using Electron Paramagnetic Resonance (EPR) with a Bruker ELEXSYS E500T spectrometer. Amplitude signals were transformed into free radical concentrations by comparing the area under the EPR absorption spectrum of the sample to that of a chloroform solution of the concentration standard, DPPH (Díaz et al ). Approximately 25 mg of lyophilized tissue from individuals sampled from each treatment were mixed with 1 mL of chloroform under an argon atmosphere.…”
Section: Methodsmentioning
confidence: 99%
“…The potential antioxidant activity of postlarval extracts was determined on the basis of the scavenging activity of the stable 1,1‐diphenyl‐2‐picryhydrazyl (DPPH) free radical, using Electron Paramagnetic Resonance (EPR) with a Bruker ELEXSYS E500T spectrometer. Amplitude signals were transformed into free radical concentrations by comparing the area under the EPR absorption spectrum of the sample to that of a chloroform solution of the concentration standard, DPPH (Díaz et al ). Approximately 25 mg of lyophilized tissue from individuals sampled from each treatment were mixed with 1 mL of chloroform under an argon atmosphere.…”
Section: Methodsmentioning
confidence: 99%
“…Aliquots of 50 µL with 50 µL of DPPH solution (1.53×10 -5 M) were analyzed at a constant room temperature of 19.85°C and at fixed time intervals for 60 min. Control or blank preparations containing 50 µL of DPPH in chloroform solvent remained unaltered after an extended period, DPPH proved to be a very stable free radical (Díaz et al, 2014); the intensity of the signal decays with time and represents the radicaltissue reaction. Amplitude signals were transformed in radical concentrations by comparing the area under the EPR absorption spectrum of the sample to a chloroform solution of the concentration standard, DPPH.…”
Section: Electronic Paramagnetic Resonance (Epr) Measurementsmentioning
confidence: 99%
“…A high concentration of total carotenoid in oocytes indicated that this micronutrient is importantly required for ovary maturation as many previous studies reported. The important function of astaxanthin in the yolk sac is probably related to its function to improve antioxidant enzyme activities which further increase the tolerance against environmental stress including salinity, pH, oxygen depletion and nitrite stress (Flores et al, 2007;Diaz et al, 2014;Wang et al, 2018) which may happen during the earlier stage of larval development.…”
Section: Fatty Acid Profile In the Meat Of Female Broodstockmentioning
confidence: 99%